2023
DOI: 10.3390/plants12101956
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Mysteries of Non-Mendelian Heredity in Plant Breeding

Abstract: Mendelian heredity is the cornerstone of plant breeding and has been used to develop new varieties of plants since the 19th century. However, there are several breeding cases, such as cytoplasmic inheritance, methylation, epigenetics, hybrid vigor, and loss of heterozygosity (LOH), where Mendelian heredity is not applicable, known as non-Mendelian heredity. This type of inheritance can be influenced by several factors besides the genetic architecture of the plant and its breeding potential. Therefore, explorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…Variable importance allows for the consideration of interaction effects between SNPs, which is advantageous in identifying associations for complex traits. Conventional GWAS methods are better at detecting SNPs with large main effects on traits but are not as effective in considering the complex biological processes that shape these traits [ 23 ]. Recent studies have shown that SNPs with high importance scores may not necessarily have significant p -values from single SNP analyses [ 71 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable importance allows for the consideration of interaction effects between SNPs, which is advantageous in identifying associations for complex traits. Conventional GWAS methods are better at detecting SNPs with large main effects on traits but are not as effective in considering the complex biological processes that shape these traits [ 23 ]. Recent studies have shown that SNPs with high importance scores may not necessarily have significant p -values from single SNP analyses [ 71 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the availability of affordable next-generation technologies, researchers are now able to capture much of the genetic variation in a given genome and generate large numbers of genomic sequences and genetic properties even in large plant populations [ 22 , 23 ]. The abundance of plant genetic sequences can be categorized as big data due to their compliance with the three Vs, which are volume, velocity, and variety [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most heavily studied epigenetic regulators are DNA methylation, histone modifications, and small RNAs (reviewed in Allis et al 2015 ). These regulators participate in such phenomena as genomic imprinting, paramutation, creation of epialleles, and RNA interference ( Heard and Martienssen 2014 ; Fitz-James and Cavalli 2022 ; Yoosefzadeh Najafabadi et al 2023 ). Epigenetic marking of genes by DNA methylation and histone modifications is subject to removal and addition in each generation in response to developmental cues and environmental influences, unlike the underlying DNA sequence.…”
Section: Some Examples Of Non-mendelian Inheritancementioning
confidence: 99%